Personalized cytomic assessment of vascular health: Evaluation of the vascular health profile in diabetes mellitus. Issue 4 (2nd August 2013) - Kurtzman, Nicholas; Zhang, Lifeng; French, Benjamin; Jonas, Rebecca; Bantly, Andrew; Rogers, Wade T.; Moore, Jonni S.; Rickels, Michael R.; Mohler, Emile R.
Abstract : Background: An inexpensive and accurate blood test does not currently exist that can evaluate the cardiovascular health of a patient. This study evaluated a novel high dimensional flow cytometry approach in combination with cytometric fingerprinting (CF), to comprehensively enumerate differentially expressed subsets of pro‐angiogenic circulating progenitor cells (CPCs), involved in the repair of vasculature, and microparticles (MPs), frequently involved in inflammation and thrombosis. CF enabled discovery of a unique pattern, involving both MPs and CPCs and generated a personalized signature of vascular health, the vascular health profile (VHP). Methods: Levels of CPCs and MPs were measured with a broad panel of cell surface markers in a population with atherosclerosis and type 2 diabetes mellitus (DM) and age‐similar Healthy controls (HC) using an unbiased computational approach, termed CF. Results: Circulating hematopoietic stem and progenitor cell (CHSPC Ang ) levels were detected at significantly lower concentrations in DM ( P < 0.001), whereas levels of seven phenotypically distinct MPs were present at significantly higher concentrations in DM patients and one MP subset was present at significantly lower concentration in DM patients. Collectively, the combination of CHSPC Ang and MP levels was more informative than any one measure alone. Conclusions: This work provides the basis for a personalized cytomic vascular health profile that may be useful for a variety of applications including drug development, clinical risk assessment and companion diagnostics. © 2013 International Clinical Cytometry Society